Dexamethasone and Training-Induced Cardiac Remodeling Improve Cardiac Function and Arterial Pressure in Spontaneously Hypertensive Rats - Duchatsch, Francine [UNESP]; Tardelli, Lidieli P. [UNESP]; Herrera, Naiara A. [UNESP]; Ruiz, Thalles F. R. [UNESP]; Vicentini, Carlos A. [UNESP]; Okoshi, Katashi [UNESP]; Santos, Carlos F.; Amaral, Sandra L. [UNESP] (Sage Publications Inc, 2020)
Introduction: Dexamethasone (DEX)-induced hypertension and cardiac remodeling are still unclear, especially in spontaneously hypertensive rats (SHR). On the other side, exercise training is a good strategy to control hypertension. Therefore, this study investigated the effects of DEX treatment and physical training on arterial pressure and cardiac remodeling in SHR. Material and Methods: SHR underwent treadmill training (5 days/week, 1h/session, at 50-60% of maximal capacity, 0% degree, 75 days) and received low-dose of DEX (50 mu g/kg,s.c.) during the last 15 days. Sedentary Wistar rats (W) were used as control. Echocardiography and artery catheterization were performed for cardiac remodeling and function, arterial pressure and autonomic nervous system analyses. In addition, left ventricle (LV) capillary density, myocyte diameter and collagen deposition area were analyzed using specific histological staining. Results: Low-dose of DEX treatment did not exacerbate arterial pressure of SHR and trained groups had lower values, regardless of DEX. DEX and training decreased relative left ventricle wall thickness (RWT) and determined LV angiogenesis (+19%) and lower collagen deposition area (-22%). In addition, it determined increased left ventricular diastolic diameter. These changes were followed by improvements on systolic and diastolic function, since it was observed increased posterior wall shortening velocity (PWSV) and reduced isovolumetric relaxation time (IVRT). Conclusion: In conclusion, this study is unique to indicate that low-dose of DEX treatment does not exacerbate arterial pressure in SHR and, when associated with training, it improves LV systolic and diastolic function, which may be due to LV angiogenesis and reduction of wall collagen deposition area.
Keywords: hypertension; echocardiography; cardiac function; synthetic glucocorticoids; physical exercise